Exploring the relationship between dysfunctional metacognitive processes and orthorexia nervosa: the moderating role of emotion regulation strategies - Sarah Gerges; Vanessa Azzi; Dora Bianchi; Fiorenzo Laghi; Sara Pompili; Diana Malaeb; Sahar Obeid; Michel Soufia; Souheil Hallit (BMC Psychiatry, 2023)
Abstract Background Dysfunctional metacognitive processes and emotional dysregulation have been widely documented in the eating disorder literature. Despite numerous research and recent consensus suggesting the categorization of orthorexia nervosa as a form of eating disorder, no previous study has examined whether aberrant metacognitive processes also correlate with orthorexia nervosa tendencies. This paper investigates potential associations between symptoms of orthorexia nervosa and dysfunctional metacognitive processes while also exploring whether such relationships may be influenced by adaptive/maladaptive emotion regulation strategies. Methods We conducted a cross-sectional study in all Lebanese governorates. In total, 423 Lebanese adults completed an online questionnaire including the Teruel Orthorexia Scale, the Emotion Regulation Questionnaire, the Difficulties in Emotion Regulation Scale – 16 Item Version, and the Metacognitions Questionnaire – Short Form. Results Higher physical activity, expressive suppression, emotion regulation difficulties, positive metacognitive beliefs about worry, and need to control thoughts were significantly associated with higher orthorexia nervosa. Additionally, the emotion regulation strategies moderated the relationships between two dysfunctional metacognitive processes and orthorexia nervosa. Specifically, cognitive self-consciousness was negatively related to orthorexia nervosa only in individuals with low (versus higher) emotion suppression (maladaptive emotion regulation strategy). In contrast, negative beliefs about worry uncontrollability and danger positively predicted orthorexia nervosa only in individuals with lower (versus high) cognitive reappraisal (adaptive emotion regulation strategy). Lower socio-economic status and having a university level of education compared to secondary level were significantly associated with lower orthorexia nervosa. Conclusion Our study provides the first empirical evidence for the existence of significant associations between dysfunctional metacognitive processes and orthorexia nervosa. It also highlights that these pathways are considerably modulated by individuals’ ability to regulate their emotions adaptively versus maladaptively. Our findings thus suggest that therapies aimed at improving thought monitoring and emotional regulation may be beneficial for individuals with symptoms of orthorexia nervosa.